Reviews. (1st March 2015) - Menchen-Trevino, Ericka; Timan, Tjerk; Al-Rawi, Ahmed
The Hidden Agenda of the Political Mind: How Self-Interest Shap es Our Op inions and Why We Won't Admit it, Jason Weeden and Robert Kurzban (2014) 1st ed., Princeton, NJ: Princeton University Press, 376 pp., ISBN: 9780691161112, h/bk, $29.95; ISBN: 9781400851966, e-bookThe Data Revolution: Big Data, Op en Data, Data Infrast ructures and Their Consequences, Rob Kitchin (2014) 1st ed., London: Sage, 240 pp., ISBN: 9781446287484, p/bk, £22.99; ISBN: 9781446287477, h/bk, £65.00; ISBN: 9781473908260, e-book (http://www.uk.sagepub.com/books/Book242780?subject=F00&fs=1)Media Fram ing of the Muslim World: Conflicts, Crises and Contexts, Halim Rane, Jacqui Ew art and John Martinkus (2014) 1st ed., London: Palgrave Macmillan, 216 pp., ISBN: 9781137334824, p/bk, 18.99 pounds; ISBN: 9781137334817, h/bk, 60 pounds (http://www.palgrave.com/page/detail/media-framing-of-the-muslim- world-halim-rane/?K=9781137334817)